Integrasi Filsafat Dan Pendidikan: Landasan Teoritis Dalam Pendidikan Islam - `Alin Nur Salsabila; Ayu Shaumina Mubarakah; M.Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research discusses educational philosophy in the context of Islamic education, by highlighting Harold Titus' critical thinking about the nature of existence and life. Islamic education integrates the principles of this philosophy through the concepts of at-Tarbiyah, at-Ta'lim, and at-Ta'dib, which include cognitive, emotional and spiritual development. At-Tarbiyah emphasizes character formation through various methods such as modeling and habits, while at-Ta'lim focuses on the transfer of knowledge which also develops moral character. At-Ta'dib integrates knowledge and morality to form socially and ethically responsible individuals. This research emphasizes the importance of a holistic approach in Islamic education to form individuals who are academically competent and have noble character.